Sustainable Education Assessment ABK Viewed from The Condition Physical Characteristics of Regional, Social, and Economic Community in Underdeveloped Area Ranah Batahan, Pasaman Barat District, Indonesia - Arsida Nur; Nur Azizah Safii (International Journal of Educational Dynamics, 2019)
The problem in this research study originated from education of ABK in the rural area, Ranah Batahan Sub-district of Pasaman Barat. There were many problems related to the continuity of education of ABK in this area. The research used mixed method (combined) to collect the data besides. It conducted an observations and interviews to reinforce the data. The respondents were chosen by using total sampling and for the techniques of data analysis; it used reduction, display, verification test of validity and reliability. To find the solution of this problem the researcher with a FGD (focus group discussion) together with principals, teachers, and UPTPD of Ranah Batahan Sub-district. From the research the result showed that the physical characteristic of the area was difficult to reach. From the social side, the research showed that there is not enough concern guides by the parents of ABK. So that ABK had a low motivation to continue their study. Besides, there were problem in economic community education the research showed. In this area, most of the people had a problem related to the cost for the education of ABK. It was also constrained to the sustainability of education of ABK. So that it was important to give an effort to continuity education of ABK in Ranah Batahan Sub-district. For example, it was conducted by building a SLB together with the parents of ABK, people, head master, and also the government.